Pattern of Skin Diseases among the Outpatients of a Tertiary Care Hospital, Chattogram - Ahmed, Shalahuddin; Bintha Mannan, Shamsun Nahar (IAHS Medical Journal, 2024)
Background: Skin diseases are broad range of conditions affecting the skin and diseases caused by bacterial, viral, fungal infection, allergic reactions, Ca-skin and parasites. Pattern of skin disease in generally determined by various ecological factors. The prime objective of the study was to determine the pattern of skin disease among the Outpatients of Bangabandhu Memorial Hospital, Chattogram. Material and methods: This was a retrospective type of study, was conducted in the Department of Dermatology and Venerology, Bangabandhu Memorial Hospital, Chattogram during the period from July 2022 to December 2022. A total number of 300 patients of OPD were selected as a study population. Among them, 129 patients were male and 171 patients were female. Results: A total number of 300 patients was selected by random sampling for the study. Majority of them were female 171(57%) and 129(43%) were male. Among infective skin diseases, scabies, tinea infection, pityriasis versicolor and pyoderma was found in 12% (36), 10.66% (32), 3.33% (10) and 4.33% (13) patients respectivily. Here scabies was major presentation. Among noninfective skin diseases, eczema, psoriasis, acne vulgaris, urticaria was found in 13.66% (41), 3.33% (10), 9% (27) and 6% (18) patients respectivily. Here eczema emerged as commonest group disorders. Conclusion: From the study it may conclude that the prevalence of non-infective skin diseases is higher than that of infective skin diseases. IAHS Medical Journal Vol 6(1), June 2023; 58-61